TEACHING ENGLISH SPEAKING THROUGH INFORMATION GAP TECHNIQUE (A Classroom Action Research at the 8th Grade Students of Madrasah Tsanawiyah Al-Husna Depok) - Yanti Rosalinah; Nurul Khilda (LPPM Universitas Bina Sarana Informatika, 2019)
Abstract: Speaking is an important skill in learning English. However, the teacher still need an appropriate technique to teach speaking. So that, the writer used Information Gap technique in learning English speaking. This study aims to apply Information-Gap techniques in teaching speaking English in 8th grade students at MTs.Al-Husna Depok. In this study, the writer uses A Classroom Action Research (CAR). The writer analyzes and collects data during the teaching process through; interviews, observation, literature study, and the internet. Moreover, in order to collect the result of the significant differences before and after of using Information Gap, the writer uses pre-test and post-test during the observation. The research findings include: 1) Information Gap is an interesting technique in learning speaking, so that the students can enjoy the learning process. 2) With the Information Gap technique can make students more active in communication, and increase the courage and confidence of students. 3) In addition, by applying this technique students do not feel bored, because there are many different and interesting activities in Information Gap technique. So, it can be concluded that the Information Gap technique is very effective in teaching English speaking to students. Keyword: Teaching, Speaking, Information Gap TechniqueAbstract: Speaking is an important skill in learning English. However, the teacher still need an appropriate technique to teach speaking. So that, the writer used Information Gap technique in learning English speaking. This study aims to apply Information-Gap techniques in teaching speaking English in 8th grade students at MTs.Al-Husna Depok. In this study, the writer uses A Classroom Action Research (CAR). The writer analyzes and collects data during the teaching process through; interviews, observation, literature study, and the internet. Moreover, in order to collect the result of the significant differences before and after of using Information Gap, the writer uses pre-test and post-test during the observation. The research findings include: 1) Information Gap is an interesting technique in learning speaking, so that the students can enjoy the learning process. 2) With the Information Gap technique can make students more active in communication, and increase the courage and confidence of students. 3) In addition, by applying this technique students do not feel bored, because there are many different and interesting activities in Information Gap technique. So, it can be concluded that the Information Gap technique is very effective in teaching English speaking to students. Keyword: Teaching, Speaking, Information Gap Technique